Membumikan Teori Negara Kesejahteraan Dalam Penguatan Dana Desa Untuk Pengentasan Kemiskinan Menurut Keadilan Distributif - Arifin, Muhammad Zainul; Nugraha, Muslim; Yunithia Putri, Taufani; Ramadhan, Muhammad Syahri (CV. Cendikiawan Muda Sriwijaya, 2024)
Prosperity and welfare have been ideals pursued by the founders of this nation and the current Indonesian government. These ideals are manifested in the preamble of the 1945 Constitution, which states: